BCS-BEC crossover and nodal points contribution in p-wave resonance superfluids - Kagan, M.Yu.; Efremov, D.V. (Физика низких температур, 2009)
We solve the Leggett equations for BCS–BEC crossover of the resonance p-wave superfluid. We calculate sound velocity, specific heat and the normal density for the BCS-domain (μ > 0), BEC-domain (μ < 0) as well as for the interesting interpolation point (μ = 0) in the triplet A₁-phase in 3D. We are especially interested in the quasiparticle contribution coming from the zeroes of the superfluid gap in the A1-phase. We discuss the spectrum of orbital waves and the superfluid hydrodynamics at temperature T → 0. In this context we elucidate the difficult problem of chiral anomaly and mass-current nonconcervation appearing in the BCS-domain. We present the different approaches to solve this problem. To clarify this problem experimentally we propose an experiment for the measurement of anomalous current in superfluid A1-phase in the presence of aerogel for ³He and in the presence of Josephson tunneling structures for the ultracold gases in magnetic traps.